New Methyl Methacrylate Derived Adsorbents – Synthesis, Characterization and Adsorptive Removal of Toxic Organic Compounds - Monika Wawrzkiewicz, Beata Podkościelna, Przemysław Podkościelny and Jadranka Blazhevska Gilev (Wiley-VCH GmbH, 2023)
This study aimed to synthesize polymeric adsorbents by suspension polymerization using methyl methacrylate (MMA) with different crosslinking monomers. Divinylbenzene (DVB) and aliphatic monomers: ethylene glycol dimethacrylate (EGDMA) or N,N’-methylenebisacrylamide (NN) containing additional amide groups were used. The possibility of using the prepared copolymers (MMA-NN, MMA-EGDMA, MMA-DVB) as adsorbents for the removal of toxic compounds such as dyes (C.I. Acid Red 18 (AR18), C.I. Acid Green 16 (AG16), C.I. Acid Violet 1 (AV1), C.I. Basic Yellow 2 (BY2), C.I. Basic Blue 3 (BB3) and C.I. Basic Red 46 (BR46)) and phenol (PhOH) from dye baths and effluents was evaluated. Preferential adsorption of basic-type dyes compared to acid-type dyes or phenol was observed by the polymers. Adsorbent based on MMA-EGDMA exhibited the highest capacity for investigated dyes and phenol. The pseudo-second order kinetic model as well as the intraparticle diffusion model can find application in predicting sorption kinetics. Based on the equilibrium sorption data fitted to the Langmuir, Freundlich, Temkin and Dubinin-Radushkevich model, uptake of BB3, AV1 and PhOH is rather physisorption than chemisorption. The regeneration yield of MMA-EGDMA does not exceed 60 % using 1 M HCl, 1 M NaCl, and 1 M NaOH in 50%v/v methanol.
Keywords: polymeric adsorbents